Media Belajar Interaktik Komunikatif Pada Anak Usia Dini Dengan Kartu Bergambar Kegiatan Sehari-hari Di Taman Kanak-Kanak - Alice Zellawati; Siska Adinda Prabowo Putri (IMAGE, 2021)
Early childhood education is very important and as a basis for subsequent developments. Communication is formed from simple words to complex sentences. Developing vocabulary skills in pre-school children is one of the crucial aspects of development for early childhood. This study aims to optimize communication skills in early childhood through communicative interactive learning media in early childhood with picture cards of daily activities in kindergarten. The study was conducted in 20 kindergartens in Central Semarang. The research method used is the quasi experimental method. Data collection techniques using pretest, posttest, observation, interviews with teachers and parents, and documentation. The results of this study are an increase in the interactive communication skills of TK A children through the media of picture cards in developing their language skills.